Answer:
Yuh
Step-by-step explanation:
Answer:
-2
Step-by-step explanation:
You multiply each term by -2 to get the next term.
To find this for this sequence, divide the term on the right by the term on the left.
8 / -4 = -2 or -4 * -2 = 8
-16 / 8 = -2 or 8 * -2 = -16
32 / -16 = -2 or -16 * -2 = 32
-64 / 32 = -2 or 32 * -2 = -64
Answer:
would be the correct statement.
Step-by-step explanation:
As we know that
Average rate of change = Change in output / Change in input
= Δy / Δx
![=\frac{y_{2} -y_{1}}{x_{2} -x_{1}}](https://tex.z-dn.net/?f=%3D%5Cfrac%7By_%7B2%7D%20-y_%7B1%7D%7D%7Bx_%7B2%7D%20-x_%7B1%7D%7D)
![=\frac{g(x_{2})-g(x_{1})}{x_{2}-x_{1}}](https://tex.z-dn.net/?f=%3D%5Cfrac%7Bg%28x_%7B2%7D%29-g%28x_%7B1%7D%29%7D%7Bx_%7B2%7D-x_%7B1%7D%7D)
As the average rate of change of g(x) between x = 4 and x = 7 is 5/6.
so
![\:Average\:rate\:of\:change\:=\:\frac{g\left(7\right)-g\left(4\right)}{7-4}](https://tex.z-dn.net/?f=%5C%3AAverage%5C%3Arate%5C%3Aof%5C%3Achange%5C%3A%3D%5C%3A%5Cfrac%7Bg%5Cleft%287%5Cright%29-g%5Cleft%284%5Cright%29%7D%7B7-4%7D)
![\frac{5}{6}=\:\frac{g\left(7\right)-g\left(4\right)}{7-4}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B6%7D%3D%5C%3A%5Cfrac%7Bg%5Cleft%287%5Cright%29-g%5Cleft%284%5Cright%29%7D%7B7-4%7D)
Therefore,
would be the correct statement.